Multilingualism Pada Landskap di Ruang Publik: Analisis Multilingualism Pada Penamaan Usaha Makanan di Kabupaten Bangkalan - Kartika Ninggar Shabrina; Fitriyatuz Zakiyah; Eka Susylowati (Journal of Social, Culture, and Language, 2023)
Multilingualism in public spaces is not only done orally, multilingualism is also found in the landscape in public spaces such as business and tourist attractions signboards. The study of language in the landscape is called landscape linguistics (LL). LL is the presence of language between space and place. This research aims to find out what language is used in naming food business places in Bangkalan Regency. This research uses qualitative method. The data of this research are photos of the names of food businesses in Bangkalan Regency, including cafes and eating places around the campus of Trunojoyo Madura University, Kamal District, and Bangkalan District. The results of this study will show the pattern of language in public spaces in Bangkalan. Keywords: Linguistic Landscape, Multilingualism, Bangkalan